"Rise of the middle of the pyramid in Africa": theoretical and practical realities for understanding middle class consumer purchase decision making. Issue 1 (7th January 2014) - Chikweche, Tendai; Fletcher, Richard
Abstract : Purpose: – The main purpose of this paper is to investigate the factors that influence the growing African middle class (middle of pyramid; MOP) consumers' purchase decision making. Design/methodology/approach: – A mixed qualitative research method approach comprising in-depth interviews was used to collect data from middle of pyramid consumers in four countries. Secondary data analysis was used to complement the interviews. Findings: – Key findings include the identification of three key intertwined influencers of branding, peer and social networks and aesthetics and product performance. Other influencers include technology and new products, distribution channels and family. Research limitations/implications: – The focus on four countries has the potential to minimize the generalizability of findings from the study although the four countries used have a significant amount of middle class consumers in Africa. However, this does not detract from the findings of the study but actually provides a basis for further research into other emerging markets. Practical implications: – Findings from the study provide practical insights for marketing managers who intend to serve this market, key of which are branding, use of social networks, online distribution and maximising technology. Originality/value: – The paper expands the research agenda of the relatively new area of the MOP. By focusing on the MOP in Africa, the research expands existing knowledge beyond previous areas of focus of middle class studies that focus on China and India.